Control del Nemátodo Meloidogyne sp en Plántulas te Tomate (Lycopersicon Sculentum) con Extracto ce Catahua (Hura Crepitans) - Reátegui Vega, José (2003)
This research was conducted in environments URKU Studies Amazónicos, in order to seek alternative solutions to reprove the use of agrochemicals for this purpose bark Ja tree species ~ catahua existing • ta Peruvian Amazon was used. The main objective was to evaluate the effect of four doses of aqueous extract of bark catahua (Hura crepitans), in controlling nematode Meloidogynesp {.} In tomato seedlings. The bark of this was extracted with caution using lenses and masks to prevent blindness and stomach problems, i extract it at different concentrations (10, 20, 30 and 50%) was prepared; with an experimental design completely randomized to six treatment and four replications using contaminated soil nematodes Meloidogyne, this was obtained from the farm Oasis located in the district of Morales. Soil disinfection with catahua extract at different doses was performed three days before planting tomato Ja. The results are favorable to extract treatment Catahua 50% being the dose of higher concentration compared to treatments lower concentration 10%, 20% and 3CV% counterstained with two witnesses, the first with chemical control and second witness without aqueous extract, obtained favorable results with the chemical control, which exerted a similar control to treatment with 50% concentration of extract.